2011
DOI: 10.1038/leu.2011.240
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic transplantation following a reduced-intensity conditioning regimen in relapsed/refractory peripheral T-cell lymphomas: long-term remissions and response to donor lymphocyte infusions support the role of a graft-versus-lymphoma effect

Abstract: Rescue chemotherapy or autologous stem cell transplantation (autoSCT) gives disappointing results in relapsed peripheral T-cell lymphomas (PTCLs). We have retrospectively evaluated the long-term outcome of 52 patients receiving allogeneic SCT for relapsed disease. Histologies were PTCL-not-otherwise specified (n ¼ 23), anaplastic large-cell lymphoma (n ¼ 11), angioimmunoblastic T-cell lymphomas (n ¼ 9) and rare subtypes (n ¼ 9). Patients were allografted from related siblings (n ¼ 33, 64%) or alternative donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
100
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 23 publications
7
100
2
2
Order By: Relevance
“…In the largest series of patients treated with DLI for cutaneous T-cell lymphoma, preceded by chemotherapy or radiotherapy for 5 of 12 patients, a response was observed in 8 patients. 5 A response to DLI has also been reported in a small number of patients with non cutaneous TCL. [4][5][6]8 Itonaga et al 13 recently reported results for 35 patients who relapsed after allo-SCT for adult T-cell leukemia/lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the largest series of patients treated with DLI for cutaneous T-cell lymphoma, preceded by chemotherapy or radiotherapy for 5 of 12 patients, a response was observed in 8 patients. 5 A response to DLI has also been reported in a small number of patients with non cutaneous TCL. [4][5][6]8 Itonaga et al 13 recently reported results for 35 patients who relapsed after allo-SCT for adult T-cell leukemia/lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, some data suggest a beneficial allogeneic effect against PTCL. In a study by Dodero et al, 5 52 patients received second-line allografts with RIC. The OS rate among patients with chemoresistant disease before the graft was 29% at 5 years, suggesting a persistent GvL effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations